Grundtvigs skoleverden ved K. E. Bugge - Holm, Søren (Grundtvig-studier, 1970)
Grundtvigs skoleverden, i tekster og udkast. Ed. by K. E. Bugge. I—II.Rev. by Søren Holm This edition is a collection of the most important parts of Grundtvig’s writings on education, and it has been made by a very competent editor. Mr. Bugge knows Grundtvig’s ideas as well as their historical background, the selection is reasonable, and the get-up is very attractive. Grundtvig’s belief in the spoken word was too strong for him to trust a particular method. Methods may be delusions and mistakes, and, like forms of government, they belong to specific periods. In “Lærebog i verdenshistorien for de tvende øverste klasser i Schouboes Institut” ( 1807) (A History of the World for the two Upper Forms in Schouboe’s School), which he dictated to the pupils, his view on examinations is quite sober: they should be kept in mind, but our real aims are higher. In the same period Grundtvig says about country schools that the villager has the same ultimate objectives as other people. He does not have the time to ponder everything, but then he is entitled to demand that other people should make their results accessible to him. He needs geography rather than natural history. But the clergymen, who were to be the pioneers of knowledge, seem to be more interested in farming. Judging from his “ Leksjons- og karakterbog for den unge Stensen Leth” (Report on the lessons of young Stensen Leth) from 1806—here published for the first time— Grundtvig appears to have done a solid piece of work for his salary at Egeløkke. - Several of the later essays are concerned with “the school at Sorø”, others with universities, education of the people, citizenship, and general education. Grundtvig’s capacity for work was inconceivable.